2021
DOI: 10.1016/j.ssmph.2021.100884
|View full text |Cite
|
Sign up to set email alerts
|

Do associations between education and obesity vary depending on the measure of obesity used? A systematic literature review and meta-analysis

Abstract: Background Consistent evidence suggests a relationship between lower educational attainment and total obesity defined using body mass index (BMI); however, a comparison of the relationships between educational attainment and total obesity (BMI ≥30 kg/m 2 ) and central obesity (waist circumference (WC) > 102 cm for men and WC > 88 cm for women) has yet to be carried out. This systematic literature review (SLR) and meta-analyses aimed to understand whether i) the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…Such difference can be explained by the level of education of our sample. It's approved that prevalence of obesity significantly decreased with level of education [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Such difference can be explained by the level of education of our sample. It's approved that prevalence of obesity significantly decreased with level of education [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were expected, since in this study a high acrylamide intake reflects a propensity to an unhealthy diet, rich in fried and roasted food, common in North American obese people and in younger populations [ 29 31 ]. Moreover, it has been reported that North American women more frequently consume healthy food such as vegetables and fruits than men [ 32 ] and that there is a strong consistent relationship between low socio-economic factors, as low scholar education, in early life and increased obesity in adulthood [ 33 ]. Furthermore, diets rich in fruit and vegetables have been shown to decrease the risk of the incidence of hip fractures [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obese knee OA patients also have a higher need for knee JRS ( 20 ) and at a younger age ( 21 ) than non-obese knee OA patients. As the association between SEP and obesity is gender specific ( 22 ), the mediating effect of obesity for the relationship between SEP and OA disease progression may also differ by gender. Longitudinal studies are needed to understand how SEP and obesity interact in the progression of OA over time.…”
Section: Introductionmentioning
confidence: 99%